2004
DOI: 10.1111/j.1432-1033.2004.04022.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interaction and cellular internalization of penetratin peptides

Abstract: Penetratin is a 16-residue peptide ] derived from the Antennapedia homeodomain, which is used as a vector for cellular internalization of hydrophilic molecules. In order to unravel the membrane translocation mechanism, we synthesized new penetratin variants. The contribution of the positively charged residues was studied by double substitutions of Lys and/or Arg residues to Ala, while the specific contribution of Trp48 and Trp56 was studied by individual substitution of these residues to Phe. Trp fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
115
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 47 publications
8
115
0
Order By: Relevance
“…It has been previously reported that peptideelipid association occurs through formation of salt bridges between the positively charged residues K4, R11 and K15 and the lipid phosphate groups [33]. In addition, tryptophan fluorescence studies previously showed the importance of peptide with positively charged residues for the initial binding to negatively charged vesicles, since double R/K / A mutations involving the residues K4/R10/ R11/K13/K15 significantly decreased the binding affinity [38]. The MEPs of 1 suggest that the above-mentioned residues (R1, K4, R11 and K15) could be responsible for the initial binding.…”
Section: Molecular Electrostatic Potentials (Meps)mentioning
confidence: 99%
“…It has been previously reported that peptideelipid association occurs through formation of salt bridges between the positively charged residues K4, R11 and K15 and the lipid phosphate groups [33]. In addition, tryptophan fluorescence studies previously showed the importance of peptide with positively charged residues for the initial binding to negatively charged vesicles, since double R/K / A mutations involving the residues K4/R10/ R11/K13/K15 significantly decreased the binding affinity [38]. The MEPs of 1 suggest that the above-mentioned residues (R1, K4, R11 and K15) could be responsible for the initial binding.…”
Section: Molecular Electrostatic Potentials (Meps)mentioning
confidence: 99%
“…To simulate protein-mediated fusion, many studies on peptide-induced membrane fusion have been conducted on model membranes such as liposomes and have employed synthetic peptides corresponding to the putative fusion sequences of viral proteins [9][10][11]. On the other hand and due to the fact that membraneassociated peptides often show a remarkable structural behaviour, the conformational study of these sequences is important to get information about their activities [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Other models, suggesting translocation of the CPPs across the lipid bilayer through stable or transiently formed pores or inverted micelles, have also been hypothesized (11). The basic nature due to the high content of arginine or lysine, the amphipathic character, and/or the presence of a hydrophobic core sequences have been suggested as important structural features of CPPs (12)(13)(14). Little is known about the cellular functions of CPPs; they have generally been studied as vectors for intracellular delivery of cargo molecules with pharmacologic potential (11,15).…”
mentioning
confidence: 99%
“…Short basic peptides referred to as cell-penetrating peptides (CPPs) 1 are able to translocate across the plasma membrane into cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several prototypical CPPs include the human immunodeficiency virus transactivator of transcription (Tat) protein and the Antennapedia homeodomain or represent oligoarginine polymers or chimeric peptides (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%